Morphological and molecular response mechanisms of the root system of different Hemarthria compressa species to submergence stress - Shen, Bingna; Li, Wenwen; Zheng, Yuqian; Zhou, Xiaoli; Zhang, Yinuo; Qu, Minghao; Wang, Yinchen; Yuan, Yang; Pang, Kaiyue; Feng, Yanlong; Wu, Jiahai; Zeng, Bing (Frontiers in Plant Science, 2024)
Hemarthria compressa is an important high-quality forage grass in southern China. In recent years, frequent flooding has caused varying degrees of impacts on H. compressa and their ecological environment. In this study, we evaluated differences in flooding tolerance between the root systems of the experimental materials GY (Guang Yi, flood-tolerant) and N1291 (N201801291, floodsensitive). We measured their morphological indexes after 7 d, 14 d, and 21 d of submergence stress and sequenced their transcriptomes at 8 h and 24 h, with 0 h as the control. The results showed that the number of adventitious roots and root length of GY and N1291 showed an increasing trend during the submergence stress period, but the overall growth of GY was significantly higher than that of N1291. RNA-seq analysis revealed 6046 and 7493 DEGs that were identified in GY-0h vs GY-8h and GY-0h vs GY-24h, respectively, and 9198 and 4236 DEGs identified in N1291-0h vs N1291-8h and N1291-0h vs N1291-24h, respectively. The GO and KEGG enrichment analysis results indicated the GO terms mainly enriched among the DEGs were oxidation-reduction process, obsolete peroxidase reaction, and other antioxidant-related terms. The KEGG pathways that were most significantly enriched were phenylpropanoid biosynthesis, plant hormone signal transduction etc. The genes of transcription factor families, such as C2H2, bHLH and bZIP, were highly expressed in the H. compressa after submergence, which might be closely related to the submergence adaptive response mechanisms of H. compressa. The results of this study provide basic data for analyzing the molecular and morphological mechanisms of H. compressa in response to submergence stress, and also provide theoretical support for the subsequent improvement of submergence tolerance traits of H. compressa.